Estudos de reformulação dos métodos de contratação, fiscalização e recebimento de poços profundos destinados a abastecimento público, no Estado de São Paulo - Nogami, Paulo Soichi (1967)
Water supply systems utilizing ground water are very advantageous in the State of São Paulo because of the low cost solution and the existence of good hydrogeologic conditions. However, well construction techniques are still well behind when compared to the stage of progress achieved by other sanitary engineering activities. No particular progress has been noticed in state agencies with respect to well construction or ground water resources evaluation methods in the last 30 years. There are two institutions under state administration wich are connected to well construction. One of them is the Instituto Geográfico e Geológico where some engineers and geologists work. Old rigs for drilling wells are employed for public and private purposes. The action of the institution is mainly directed to geological surveys. The Departamento de Obras Sanitárias gives technical assistance in designing, constructing and operating municipal water and sewage systems in interior towns of the state. Deep wells as part of water supply systems are drilled by contractors following the specifications made by state engineers. Each phase of well construction procedures performed by Departamento de Obras Sanitárias is described in detail, including considerations on design, bid preparation for drillers contracting as well as the inspection and payment to the contractor. It is given emphasis to the fnct that occasional inspections made by engineers with wide working range are not enough for obtaining correctly constructed wells, but it is still necessary to give a more close assistance to field operations if better results are to be expected. Difficulties and failures have been noticed as consequence of unsuitable standards and specifications for design and construction of wells and the lack of defined responsabilities ascribed to each section of Departamento de Obras Sanitárias, on dealing with well design and construction procedures. In order to change that inadequate status, the creation of a new section or group with specialists to operate only well design and construction is suggested. This is considered a very special kind of activity that nas to be dealed by people rather by those engaged in other water works construction programs. The group will not make regular researches and investigations on ground water resources, wich will be the scope of other institution. Considerations are being made on the formation of the group of specialists in Departamento de Obras Sanitárias and on preparing new standards and specifications for bidding and contracting. A tentative standard prepared by the author concerning deep well location, its design and construction is included on and appendix.